Effect of biomechanical constraints in the hand laterality judgment task: where does it come from? - Vannuscorps, Gilles; Pillon, Agnesa; Andres, Michael (Frontiers in Human Neuroscience, 2012)
Several studies have reported that, when subjects have to judge the laterality of rotated hand drawings, their judgment is automatically influenced by the biomechanical constraints of the upper limbs. The prominent account for this effect is that, in order to perform the task, subjects mentally rotate their upper limbs toward the position of the displayed stimulus in a way that is consistent with the biomechanical constraints underlying the actual movement. However, the effect of such biomechanical constraints was also found in the responses of motor-impaired individuals performing the hand laterality judgment task, which seems at odds with the “motor imagery” account for this effect. In this study, we further explored the source of the biomechanical constraint effect by assessing the ability of an individual (DC) with a congenital absence of upper limbs to judge the laterality of rotated hand or foot drawings. We found that DC was as accurate and fast as control participants in judging the laterality of both hand and foot drawings, without any disadvantage for hands when compared to feet. Furthermore, DC’s response latencies for hand drawings were influenced by the biomechanical constraints of hand movements in the same way as control participants’ response latencies. These results suggest that the effect of biomechanical constraints in the hand laterality judgment task is not strictly dependent on “motor imagery” and can arise from the visual processing of body parts being sensitive to such constraints.